Bidders’ strategic timing of acquisition announcements and the effects of payment method on target returns and competing bids - Chen, Sheng-Syan; Chou, Robin K.; Lee, Yun-Chi (Journal of Banking & Finance, 2011)
Using a sample of acquisition announcements released during trading versus nontrading hours, this study examines how the strategic timing of acquisition announcements determines the impact of the method of payment on target stock returns and competition among bidders. For overnight acquisition announcements, we find that cash payment offers positively and significantly affect acquisition premiums and target returns, yet these results do not hold for daytime announcements. Cash payment offers made during nontrading hours are more likely to deter potential bidders and complete proposed transactions. However, we find no such relationship for daytime announcements. These findings suggest that the timing of acquisition announcements by bidders is important for assessing the effects of payment method as a signal of target valuation and a preemption of competing bids.